3D Research Challenges in Cultural Heritage IV Risk Prevention and Monitoring Methods - Ioannides, Marinos; Issini, Giovanni; Oliveira, Daniel; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open access book presents a collection of papers focusing on a range of digital technologies and their use in the protection and restoration of cultural heritage. Digital tools - from 3D scanning and photogrammetry to Heritage Building Information Modeling (HBIM), Digital Twins, and Extended Reality (XR) - are transforming the way we understand and care for tangible heritage. These technologies are applied to both record the physical form and material conditions of a site and to permit simulations of deterioration, design interventions, and careful reconstruction. A central theme of this volume is post-disaster restoration and how the scientific and technical aspects of restoration can be made accessible to a broader audience through innovative visualizations, interactive platforms and storytelling. Digital tools should not only serve experts but also allow the public to participate both on-site and remotely via the web. This book advocates a holistic approach to heritage management, combining cutting-edge technology with local knowledge, risk analysis with creative reuse, and positioning the act of restoration as a bridge connecting the past, present and future.
On the Use of HBIM for the Analysis of Historical Constructions: Technical and Semantic Interoperability for Different Aspects of the Structural Assessment -- The key role of structural health monitoring as a control tool in the post-earthquake recovery phase of damaged heritage buildings: The case study of "Collegiata di Santa Maria" in Visso, Italy -- Understanding and managing risk in historic areas: A multi-hazard vulnerability assessment of the Historic City Centre of Guimarães, Portugal -- Digital guardians: A new method of data management for at-risk cultural heritage in Bavaria -- Risks and Responsibilities: The German Tendaguru Collection as Chiltural Heritage and its 3D Digitisation -- AI-Driven Analysis in Point Clouds for Archaeological Documentation -- Digital Preservation and Restoration of Historic Buildings in Agadez, Niger -- Digital Humanities and Physics Applied to the Study of Cultural Heritage Objects: the case of ex-votos -- "Fostering Community-Cultural Heritage Resilience in Post-Disaster Scenarios: Merging Hands-On Experience with Digital Technologies in the OPHERA Project" -- Digital tools for assessment and communication of historic architectural heritage restoration project: The case study of Palazzo Saladini di Rovetino in Ascoli Piceno, Italy -- Preserving and Communicating a Sudanese Heritage Site through a Digital Exhibition -- Digital Heritage Documentation for Protecting and Rebuilding Tangible Heritage in Natural Disaster and Conflict Zones -- Restoration and Digitisation of the Tarxien Stone Bowl: A Multidisciplinary Approach.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Digital humanities; Virtual reality; Augmented reality; Image processing -- Digital techniques; Computer vision; Building information modeling; Cultural property; Archaeology; Digital Humanities; Virtual and Augmented Reality; Computer Imaging, Vision, Pattern Recognition and Graphics; Building Information Modeling; Cultural Heritage; Heritage Management